Music production management at SMA Negeri 1 Kanangan Kediri - Itot, Itot Bian Raharjo (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
Higher Education is a scientific institution that has the main task of implementing the Tri Dharma of Higher Education, namely education and teaching, research, and community service. Through the tasks it carries, it is hoped that the Higher Education Institution will become a center for the development of the whole human being as well as the maintenance and development of science, technology, and art in accordance with the needs both in the present and in the future. Similar to Higher Education, in order to implement the Tri Dharma of Higher Education – Community Service, various activities will be carried out in the form of